Juridical Analysis of Presidential Term Extension Through Constitutional Amendment - Rety Bella Octavya Zain; Catur WIdo Haruni; Sholahuddin Al-Fatih; Mohammad Al An'imat (Universitas Muhammadiyah Malang, 2023)
One of the content materials in constitutional amendment process is Article 7 of 1945 Republic of Indonesia Constitution concerning the President's term of office being limited to only two terms. During the era of President Joko Widodo's leadership, the issue of extending presidential term into three terms resurfaced. This study raises the main issues studied are, First, how is the legal politics of extending the President's term of office in terms of the Presidential Government System. Second, what is the urgency of President's term extension in terms of the Presidential System. This research is a normative juridical research with legal materials. The approach method used is the statutory approach and the conceptual approach. This study uses a qualitative descriptive analysis technique. Based on the results of research and discussion, that First, legal politics in extending the presidential term of office, namely placing a place to filter leaders so they can advance in a direct democratic party has a logical consequence so that in a presidential system of government, the existence of political parties can certainly have an influence on support on every presidential policy taken. Second, the urgency of an extension of the term of office of President in terms of Presidential Government system, that there is no need to extend the term of office for three terms because it causes discontinuity regarding the terms of office of the President and Vice President in Indonesia in order to prevent authoritarianism. The advice from this paper is that the extension of the term of office of the President and Vice President is sufficient for 2 periods and there is no need for an extension of the term of office of the President for more than two consecutive terms, because it can lead to abuse of power.